2018
DOI: 10.1093/toxsci/kfy147
|View full text |Cite
|
Sign up to set email alerts
|

The Bile Sequestrant Cholestyramine Increases Survival in a Rabbit Model of Brodifacoum Poisoning

Abstract: Patients exposed to long acting anticoagulant rodenticides (LAARs) are typically administered large amounts of oral vitamin K1 (VK1) to counteract life-threatening anticoagulant effects. Although VK1 treatment effectively prevents mortality, additional methods are needed to reduce the long duration of VK1 treatment which can last for months at high expense. We developed a model of brodifacoum (BDF) poisoning, one of the most potent LAARs, in adult male New Zealand White (NZW) rabbits. The LD50 for oral BDF was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Although all potential confounding factors relating to the nature of blood sample collection in the present study must be considered, trends in matched liver and serum concentrations could reflect agreement with overall SGAR toxicokinetic data in other species that show that both liver and serum levels rise and begin to decline rapidly soon after ingestion, with liver residues being much higher and persisting over a more prolonged time (Bachmann and Sullivan 1983; Huckle et al 1988; Woody et al 1992; Vandenbroucke et al 2008; Enouri et al 2015; Lindeblad et al 2018). Liver and serum levels of brodifacoum were significantly positively correlated, with the same bird having the highest concentrations of brodifacoum in both liver and serum, at 930 and 65 ng/g, respectively.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although all potential confounding factors relating to the nature of blood sample collection in the present study must be considered, trends in matched liver and serum concentrations could reflect agreement with overall SGAR toxicokinetic data in other species that show that both liver and serum levels rise and begin to decline rapidly soon after ingestion, with liver residues being much higher and persisting over a more prolonged time (Bachmann and Sullivan 1983; Huckle et al 1988; Woody et al 1992; Vandenbroucke et al 2008; Enouri et al 2015; Lindeblad et al 2018). Liver and serum levels of brodifacoum were significantly positively correlated, with the same bird having the highest concentrations of brodifacoum in both liver and serum, at 930 and 65 ng/g, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Data in laboratory rodents as well as in nonrodent mammals indicate that, in general, concentrations of ARs rise rapidly in serum or plasma as well as in liver soon after administration. However, the concentrations of ARs in serum or plasma are much lower than in liver, and these concentrations decline rapidly, with the highest levels occurring from 12 h to 3 d postadministration depending on species (Bachmann and Sullivan 1983; Huckle et al 1988; Woody et al 1992; Vandenbroucke et al 2008; Enouri et al 2015; Lindeblad et al 2018). Brodifacoum has been shown to be an exception to this pattern in laboratory mice (Vandenbroucke et al 2008) and rats (Bachmann and Sullivan 1983), displaying relatively slower disappearance from plasma and serum, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Cohn et al (22) showed that treatment with oral cholestyramine, an FDA-approved, safe and efficacious, gut-restricted, anion-exchange resin indicated for the treatment of hypercholesterolemia, significantly reduced the half-life of chlordecone, a lipophilic organochlorine pesticide, in blood and fat of industrial workers that were exposed to substantial amounts of this toxin for several months. To this end, oral cholestyramine has been recently shown to reduce mortality of rabbits with acute brodifacoum poisoning (23).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with compounds that reduce recirculation, such as bile sequestrants, could be considered for use alone or in conjunction with ILE, to lower total body brodifacoum burden by accelerating clearance from the gut. In support of this, we showed that administration of the bile sequestrant cholestyramine to brodifacoum-poisoned rabbits increased survival to almost 100% [ 38 ]. Approaches that utilize other scavengers to sequester circulating brodifacoum, or reduce its binding to serum albumin, allowing for increased redistribution to the liver, should be considered.…”
Section: Should Cytochrome P450 Inducers Be Used To Increase Long-actmentioning
confidence: 96%